Metrics of salbutamol use as predictors of future adverse outcomes in asthma - Patel, Mitesh; Pilcher, Janine; Reddel, Helen K.; Pritchard, Alison; Corin, Andrew; Helm, Colin; Tofield, Christopher; Shaw, Dominick; Black, Peter; Weatherall, Mark; Beasley, Richard (Wiley, 2013)
Background